Montessori-Based Learning Management in Developing Early Childhood Independence - Sofi Putri Nirmalasari; Arini Dwi Cahyani (Journal of Practice Learning and Educational Development, 2026)
Parental awareness in paying attention to child development is an urgency to choose an early childhood education (ECE) institution based on the child's nature. This study has the following objectives: (1) To find out the planning of Montessori-based learning in developing the independence of early childhood, (2) the implementation of Montessori-based learning in developing the independence of early childhood, and (3) the evaluation process of Montessori-based learning in developing the independence of early childhood. The approach of this study is descriptive qualitative, using in-depth interview study techniques, participatory observation, and documentation involving the principal, two teachers, and one parent. This study was conducted at the Tiny Ladybug Education Center in Semarang. The results of the study show that (1) the planning process at the Tiny Ladybug Education Center is carried out by adjusting the needs of children according to their age, (2) Implementation of learning by preparing a structured environment (prepared environment), independent learning activities, and teaching life skills. Evaluation of learning involves schools and parents with the aim of mutual elaboration.